The persuasion of performative technologies: constructing calculating selves in universities - Funck, Elin K. (Emerald, 2025)
Purpose
This paper aims to investigate the process by which performative technologies (PTs), in this case accreditation work in a business school, take form and how humans engage in making up such practices. It studies how academics come to accept and even identify with the quantitative representations of themselves in a translation process.
Design/methodology/approach
The research involved a longitudinal, self-ethnographic case study that followed the accreditation process of one Nordic business school from 2015 to 2021.
Findings
The findings show how the PT pushed for different engagements in various phases of the translation process. Early in the translation process, the PT promoted engagement because of self-realization and the ability for academics to proactively influence the prospective competitive milieu. However, as academic qualities became fabricated into numbers, the PT was able to request compliance, but also to induce self-reflection and self-discipline by forcing academics to compare themselves to set qualities and measures.
Originality/value
The paper advances the field by linking five phases of the translation process, problematization, fabrication, materialization, commensuration and stabilization, to a discussion of why academics come to accept and identify with the quantitative representations of themselves. The results highlight that the materialization phase appears to be the critical point at which calculative practices become persuasive and start influencing academics’ thoughts and actions.